The material and ideological base of the old Babylonian state: history, economy, and politics - Pecha, Lukáš (Lexington Books, 2018)
Cover; The Material and Ideological Base of the Old Babylonian State; The Material and Ideological Base of the Old Babylonian State History, Economy, and Politics; Copyright; Contents; Abbreviations; Chapter 1; Sources; Main Types of Written Sources; Administrative Texts; Contracts; Letters; Royal Inscriptions; Legal Texts; Historiographical Texts; Year Names; Oaths; Legends on Seals; Judicial Protocols; Royal Hymns; The Appearance of Texts; Notes; Chapter 2; A Summary of Political History; Humble Inceptions (from Sumu-abum to Sîn-muballiṭ); The Building of the State (Ḫammu-rabi)